Estruturas de governança corporativa e financial distress: há relação entre conselho de administração e empresas em financial distress? - Oshiro, Renan Kenji (2016)
In this master’s thesis it was analyzed if there is a significant relationship among governance structures (structure and board composition) and financial distress. This essay focused on this issue because academic studies in corporate governance and its relation to financial distress are still largely unexplored. In addition, the topic has relevance in the corporate world, since understanding which board structures and its compositions would be more efficient to avoid financial distress is attractive for many stakeholders, mainly for shareholders and creditors. To check the existence of this relationship, it was used data from Brazilian public companies and logit models of financial distress were developed. With financial distress as response variable and starting from a base model with financial control variables, new determinants and combinations of these variables were added step by step to set up intermediate models. At last, the final model included all relevant explanatory variables. The variables can be classified into governance structure variables (DUA, GOV and COF), board quality (QUA) and ownership structure (PRO1 and PRO2). The following base models were used: Daily and Dalton (1994a) and an own model, which was developed to model better financial distress and its relation to the governance structure variables. In several tested models, significant relationships were found in the percentage of dependent directors (GOV), percentage of education’s elite directors (QUA), percentage of discriminated stock (PRO1) and percentage of relevant state stock ownership (PRO2). Hence, the hypothesis that more dependent directors, less education’s elite directors and less concentrated ownership structures contribute to a future financial distress situation cannot be rejected. On the other hand, in dummy variables as duality (DUA) and supervisory board (COF) were not found statistical significance